Who is fitting better to Portuguese local demand for public choice: Central government or municipal governments? - Jose Manuel Cruz (European Regional Science Association (ERSA), 2002)
Using two alternative approaches to the demand for public choice - median voter and interest group competition - central government and local governments public provision to Portuguese municipalities were analysed. Two political issues under the responsability of municipal governments (current intervention and environmental resources management) were compared with two issues that depend on central government decisions (basic healthcare and undergraduate education). Empirical results show that the response of public choice to political demand is quite similar whatever is the responsible level of government. This easy-communicability between central government provision and local demand reveals some ability of central government in apprehending local specifities. However this does not imply that central government provision shall continue, because empirical results indicate that local groups are succeeded in lobbying central government. Setting up the studied case of local provision as reference, if decentralization occurs, the destruction of nationally organized lobbying will not strongly reinforce local interest group pressure. Consequently, at a national perspective, decentralization may bring public choice closer to the preferences of majority.
Keywords: 330